Pembekalan Metode Pengajaran Imla’ Bagi Pengajar Bimbingan Masuk Gontor Yogyakarta - Syaifullahil Maslul; Muhammad Amin Khizbullah; Thonthowi Thonthowi; Fajar Fithroni; Apriani Novitasari (Jurnal Pengabdian Masyarakat Madani, 2021)
The Great trust in Pondok Modern Darussalam Gontor was shown by the community by the arrival of thousands of prospective students from all over Indonesia to register and take the selection exam at Pondok Modern Darussalam Gontor. Imla material is one of the materials in the entrance exam of Pondok Modern Darussalam Gontor. Bimago Yogyakarta is an institution that organized preparation courses for prospective students of Pondok Modern Darussalam Gontor. The purpose of this service is to equip teachers to carry out Gontor entrance guidance. Bimago Yogyakarta collaborated with IKPM Yogayakarta held a briefing for teachers on the Imla' Teaching Method . This community service is carried out using a workshop method with three stages, material presentation, teaching practice and evaluation. The results of community service is using two methods of self preparation method and student as observation object in teaching of imla’ material.